Neutrophil extracellular traps infiltrate the lung airway, interstitial, and vascular compartments in severe COVID-19 - Radermecker, Coraline; Detrembleur, Nancy; Guiot, Julien; Cavalier, Etienne; Henket, Monique; d’Emal, Céline; Vanwinge, Céline; Cataldo, Didier; Oury, Cécile; Delvenne, Philippe; Marichal, Thomas (The Journal of experimental medicine, 2020)
Infection with SARS-CoV-2 is causing a deadly and pandemic disease called coronavirus disease–19 (COVID-19). While SARS-CoV-2–triggered hyperinflammatory tissue-damaging and immunothrombotic responses are thought to be major causes of respiratory failure and death, how they relate to lung immunopathological changes remains unclear. Neutrophil extracellular traps (NETs) can contribute to inflammation-associated lung damage, thrombosis, and fibrosis. However, whether NETs infiltrate particular compartments in severe COVID-19 lungs remains to be clarified. Here we analyzed postmortem lung specimens from four patients who succumbed to COVID-19 and four patients who died from a COVID-19–unrelated cause. We report the presence of NETs in the lungs of each COVID-19 patient. NETs were found in the airway compartment and neutrophil-rich inflammatory areas of the interstitium, while NET-prone primed neutrophils were present in arteriolar microthrombi. Our results support the hypothesis that NETs may represent drivers of severe pulmonary complications of COVID-19 and suggest that NET-targeting approaches could be considered for the treatment of uncontrolled tissue-damaging and thrombotic responses in COVID-19.